2019
DOI: 10.5664/jcsm.7814
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Positive Airway Pressure Level Predicts Response to Hypoglossal Nerve Stimulation for Obstructive Sleep Apnea

Abstract: Study Objectives: To determine whether therapeutic positive airway pressure (PAP) level predicts response to hypoglossal nerve stimulation (HGNS) for obstructive sleep apnea using the coprimary outcomes of apnea-hypopnea index (AHI) and 4% oxygen desaturation index. Methods: Combined cohort study from two US sleep otolaryngology training programs. Subjects were adults with AHI > 15 events/h who underwent HGNS. Eligible subjects had diagnostic preoperative sleep studies, full-night efficacy postoperative studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…Only one of our patients had an efficient CPAP pressure level <8 cmH 2 O, which is consistent with the findings of Lee et al 16 This may explain our poor outcomes with HGNS. We downloaded the 95th percentile pressure from the CPAP device smart card as performed by Lee et.al 16 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only one of our patients had an efficient CPAP pressure level <8 cmH 2 O, which is consistent with the findings of Lee et al 16 This may explain our poor outcomes with HGNS. We downloaded the 95th percentile pressure from the CPAP device smart card as performed by Lee et.al 16 …”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been reported that CPAP therapy levels ≥8 cmH 2 O are associated with a greater probability of lower HGNS responsiveness 16 . Only one of our patients had an efficient CPAP pressure level <8 cmH 2 O, which is consistent with the findings of Lee et al 16 This may explain our poor outcomes with HGNS. We downloaded the 95th percentile pressure from the CPAP device smart card as performed by Lee et.al 16 …”
Section: Discussionsupporting
confidence: 91%
“…13,14 Recently, our group has shown that akin to MAD patients, HGNS patients with low therapeutic PAP levels are more likely to succeed compared to patients with higher pressure requirements. 15 At present, it is unclear if response to MA during DISE can similarly aid in the selection of HGNS candidates. Here we sought to answer the following research question: What is the value of mandibular advancement simulation during DISE in predicting success for HGNS, namely the response at the soft palate and lateral walls to MA?…”
Section: Introductionmentioning
confidence: 99%
“…Both therapeutic PAP level and airway opening response to mandibular advancement (MA) on DISE have been shown to predict successful treatment of OSA with a MAD 13–14 . Recently, our group has shown that akin to MAD patients, HGNS patients with low therapeutic PAP levels are more likely to succeed compared to patients with higher pressure requirements 15 . At present, it is unclear if response to MA during DISE can similarly aid in the selection of HGNS candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent 5‐year data from the Stimulation Therapy for Apnea Reduction trial demonstrated long‐term reductions of apnea‐hypopnea index (AHI) and improvement of sleep symptoms. Yet, the overall response rate (defined as AHI < 20 events/hr and >50% reduction of AHI) remains around 60%, leaving room for optimization 9,10 …”
Section: Introductionmentioning
confidence: 99%